The Influence of Work Motivation and Compensation on Employee Performance at PT. Indosat Tbk - Indra Dharma Jaya; Joddi Sathyo; Rifky Abrar Sugiharto; Joseph Onesiforus Benaya; Paramaresi Prasidyo Tirta; Octa Viola Pujiyadi Putri; Jessica Novia Sparingga; Cikita Putri Apriliana; Mursalim Mursalim (Journal of Economics and Business Letters, 2022)
The success and progress of a company cannot be separated from the role of humans as the driving force of the organization. For that manpower or human resources are very important in achieving organizational goals. Human resources are a very important element in running an organization. Especially now that the competition in the business world is getting tougher and like it or not, companies must be able to face any changes that may occur. Therefore, companies need reliable human resources who can compete and make a good contribution to the progress of the company. Employees in each company have an active role in contributing to the company. Human resources are the factors that have the most direct impact on the competitiveness of the company.